Accuracy of Weather Radar Products for Rainfall Estimation in North Sumatra Region - Tondang, Yolanda Mutiara; Situmorang, Marhaposan; Ikhsan, Tulus; Darmawan, Yahya (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The weather radar is a remote sensing-based observation tool that identifies and records rainfall. Remote sensing is a technology that determines atmospheric conditions, measures rainfall, and performs other functions. However, the accuracy of weather radar products concerning rainfall estimation need to be evaluated. This research aims to investigate the accuracy of weather radar products for rainfall estimation in North Sumatra. We analyzed the raw weather radar data using RAINBOW software for data processing. We presented the accuracy evaluation between weather data and observation data using several statistical error parameters such as the Mean Absolute Error (MAE), Mean Error (ME), and Pearson Correlation (r). The results indicate that the CMAX radar product estimates rainfall better than the PPI and CAPPI products. The CMAX product has the lowest error value and higher correlation coefficient (r), indicating its superior rainfall estimation performance.